EP202/#77 Utilization of sentinel lymph node biopsy in early stage ovarian cancer surgery. (4th December 2022) - Barakzai, Syem; Khetan, Varun; Jooya, Neda; Roman, Lynda; Wright, Jason; Matsuo, Koji
Abstract : Objectives: Sentinel lymph node (SLN) biopsy is utilized in the surgical care of many malignancies; however, its utility has not been examined in ovarian cancer. This study examined population-level trends, characteristics, and outcomes related to SLN biopsy in early-stage ovarian cancer. Methods: This is a retrospective observational cohort study querying the Surveillance, Epidemiology, and End Result Program from 2003–2018. The study population consisted of 11, 512 women with stage I ovarian cancer who had adnexectomy-based surgical staging including lymph node evaluation. Exposure allocation was based on SLN biopsy use. Main outcomes measured were (i) trends and characteristics associated with SLN biopsy use, assessed by multivariable logistic regression modeling, and (ii) overall survival, assessed with inverse probability of treatment weighting propensity scores. Results: A total of 83 (0.7%) women underwent SLN biopsy during surgery. Recent surgery (2011–2018 versus 2003–2010, odds ratio [OR] 1.64, 95% confidence interval [CI] 1.03–2.59), small tumor size (<10 versus ≥10 cm, OR 3.07, 95%CI 1.20–7.84), and Eastern United States registry area (OR 2.74, 95%CI 1.73–4.36) were independent characteristics for SLN biopsy use. The 5-year overall survival rate was 90.5% for the SLN biopsy group and 88.6% for the lymphadenectomy group (hazard ratio 0.96, 95%CI 0.54–1.73). Conclusions: SLN biopsy was rarely performed in early-stage ovarian cancer surgery during the study period and has insufficient evidence to interpret the survival effect. SLN biopsy in early-stage ovarian cancer appears to be in the early development phase, warranting further study and careful evaluation to assess feasibility and oncologic outcome.